FORECASTING PENGERJAAN BERKAS MENGGUNAKAN METODE ARIMA DAN SARIMA - Paulina Octavia; Eko Sulistyono (JURNAL SINTAK, 2023)
The National Land Agency (BPN) is a non-ministerial government agency in Indonesia which has the task of carrying out governmental tasks in the land sector in accordance with statutory provisions. BPN was formerly known as the Agrarian Office. The formation of the Batam City Land Service is an implementing element of the Batam City Government in the field of Land Affairs which is led by a Head of Service who is under and responsible to the Mayor of Batam. The Batam City National Land Agency always carries out administrative processes starting from Monday to Friday. However, currently the Batam City BPN is serving a "Weekend Service" so that it can facilitate services that cannot be served Monday to Friday. The aim of this research is to predict incoming files and work on them in January 2023. The steps taken are calling the model, then estimating the ARIMA model, then doing proof and forecasting. The results obtained are the number of files being worked on is increasing every day.